2016
DOI: 10.1002/pola.28023
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion copolymerization of substituted acetylenes for constructing optically active helical polymer nanoparticles. Synergistic effects and helicity inversion

Abstract: Copolymerizations of substituted acetylenes have been intensively studied in solution polymerization for constructing chirally helical polymers, while emulsion copolymerizations of the kind of monomers have been only scarcely reported. In the present study, chiral substituted acetylene monomer containing cholic acid group underwent emulsion copolymerizations with an achiral acetylenic monomer in the presence of rhodium catalyst, providing optically active helical copolymer nanoparticles. Synergistic effects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In 1989, Green and co-workers reported that copolymers of an achiral isocyanate with a small fraction of a chiral isocyanate exhibit a disproportionate helical bias. This phenomenon is called the sergeants-and-soldiers (S&S) effect, and numerous subsequent studies have shown that it is applicable to both covalent and supramolecular polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In 1989, Green and co-workers reported that copolymers of an achiral isocyanate with a small fraction of a chiral isocyanate exhibit a disproportionate helical bias. This phenomenon is called the sergeants-and-soldiers (S&S) effect, and numerous subsequent studies have shown that it is applicable to both covalent and supramolecular polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some interesting rules and phenomena have been observed in the copolymerization systems, including "Sergeants and Soldiers rule", [34] "Synergistic effects" [35] and "Helicity inversion". [36] They are of great significance for a better understanding of chiral polymers and further exploration in chirality-related materials and applications.…”
Section: Polymerization Of Chiral Monomersmentioning
confidence: 99%